Genome-Wide Identification and Expression Pattern Analysis of KNOX Gene Family in Orchidaceae - Zhang, Diyang; Lan, Siren; Yin, Wei-Lun; Liu, Zhong-Jian (Frontiers in Plant Science, 2022)
The establishment of lateral organs and subsequent plant architecture involves factors intrinsic to the stem apical meristem (SAM) from which they are derived. KNOTTED1-LIKE HOMEOBOX (KNOX) genes are a family of plant-specific homeobox transcription factors that especially act in determining stem cell fate in SAM. Although KNOXs have been studied in many land plants for decades, there is a dearth of knowledge on KNOX’s role in Orchidaceae, the largest and most diverse lineage of flowering plants. In this study, a total of 32 putative KNOX genes were identified in the genomes of five orchid species and further designated into two classes (Class I and Class II) based on phylogenetic relationships. Sequence analysis showed that most orchid KNOX proteins retain four conserved domains (KNOX1, KNOX2, ELK, and Homeobox_KN). Comparative analysis of gene structure showed that the exon–intron structure is conserved in the same clade but most orchids exhibited longer intron, which may be a unique feature of Orchidaceae. Cis-elements identified in the promoter region of orchid KNOXs were found mostly enriched in a function of light responsiveness, followed by MeJA and ABA responsiveness, indicative of their roles in modulating light and phytohormones. Collinear analysis unraveled a one-to-one correspondence among KNOXs in orchids, and all KNOX genes experienced strong purifying selection, indicating the conservation of this gene family has been reinforced across the Orchidaceae lineage. Expression profiles based on transcriptomic data and real-time reverse transcription–quantitative PCR (RT-qPCR) revealed a stem-specific expression of KNOX Class I genes and a broader expression pattern of Class II genes. Taken together, our results provided a comprehensive analysis to uncover the underlying function of KNOX genes in Orchidaceae.